Application of nanoparticles for the enhancement of latent fingerprints. - Sametband, Matias; Shweky, Itzhak; Banin, Uri; Mandler, Daniel; Almog, Joseph. (Chem. Commun. (Cambridge, U. K.)Chemical Communications (Cambridge, United Kingdom), 2007)
Two different types of nanoparticles dissolved in org. soln., Au stabilized by n-alkanethiols and CdSe/ZnS stabilized by n-alkaneamine, adhere preferentially to the ridges of latent fingerprints,. The gold deposits catalyze silver electroless deposition from "Silver Phys. Developer" (Ag-PD), an aq. soln. contg. silver colloids stabilized by cationic surfactants, to form dark impressions of the ridge details. The hydrophobic capped gold nanoparticles significantly improve the intensity and clarity of the developed prints compared with Ag-PD alone. Fingermarks treated with CdSe/ZnS nanoparticles can be viewed directly, due to their fluorescence under UV illumination. [on SciFinder(R)]
CAPLUS AN 2007:258552(Journal)
Keywords: cadmium selenide zinc sulfide nanoparticle alkanethiol alkaneamine fingerprint forensic; gold nanoparticle alkanethiol alkaneamine fingerprint forensic